2016
DOI: 10.1021/acs.jpclett.6b00489
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Across the Interface: A Test of Surface Activity in the Composition of Organic-Enriched Aerosols from Bubble Bursting

Abstract: Although theories have been developed that describe surface activity of organic molecules at the air-water interface, few studies have tested how surface activity impacts the selective transfer of molecules from solution phase into the aerosol phase during bubble bursting. The selective transfer of a series of organic compounds that differ in their solubility and surface activity from solution into the aerosol phase is quantified experimentally for the first time. Aerosol was produced from solutions containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(140 citation statements)
references
References 23 publications
12
120
2
Order By: Relevance
“…A similar depletion of K + in fresh sea spray aerosol (relative to Mg 2+ ) was observed by both Keene et al [2007] and Cochran et al [2016]. Presenting the data in this way clearly reveals the enrichment of Ca 2+ as particle size decreases below 1 μm in both the North Atlantic seawater and the artificial seawater.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…A similar depletion of K + in fresh sea spray aerosol (relative to Mg 2+ ) was observed by both Keene et al [2007] and Cochran et al [2016]. Presenting the data in this way clearly reveals the enrichment of Ca 2+ as particle size decreases below 1 μm in both the North Atlantic seawater and the artificial seawater.…”
Section: Resultssupporting
confidence: 73%
“…Leck and Svensson [2015 suggested that the significant enrichment of Ca 2+ in a number of ambient aerosol samples collected over the central Arctic Ocean during summer using a low pressure impactor originated from bubbles bursting in open leads. In another laboratory study, Cochran et al [2016] observed enrichment of Ca 2+ in nascent sea spray aerosol generated from artificial seawater spiked with linear carboxylates. The authors attributed this enrichment to Ca 2+ complexed to organic matter in the form of polymer gels (see Verdugo [2012] for a review on polymer gels).…”
Section: Introductionmentioning
confidence: 93%
“…The enrichment of Ca in the aerosol phase compared to the seawater composition is of the order of 500 %. A significant enrichment of calcium in the PM 1 primary marine aerosol compared to the composition of the seawater has also been reported in earlier studies (Keene et al, 2007;Cochran et al, 2016;Salter et al, 2016), with an increased enrichment with decreasing aerosol size. The study by Salter et al (2016) suggests that some calcium ions are clustering close to the sea surface (probably in the form of carbonate ions), and that if calcium is complexing to organic matter at the seawater surface, it is with minor amounts of organic compounds.…”
Section: Number and Ccn Concentrationssupporting
confidence: 81%
“…). If the surface composition is driving the water uptake at these small sizes, only minute amounts of surface-tension-reducing substances are needed to result in a notable effect29. Salter et al 24.…”
Section: Resultsmentioning
confidence: 99%